7
$\begingroup$

The following is exercise 8.2 in 3rd edition (and exercise 8.19 in 2nd edition) of Goldstein's Classical Mechanics.

Adding the total time derivative of a function of $q_i$ and t to the Lagrangian will not change the the Euler-Lagrangian equation. So if we make the following change to Lagrangian,

$$L'(q,\dot{q},t) = L(q,\dot{q},t) + \frac{dF(q_1,q_2,...,q_n,t)}{dt}$$ we can get $$ \frac{d}{dt}\frac{\partial{L'}}{\partial{\dot{q_i}}} - \frac{\partial{L'}}{\partial{q_i}} = 0 $$ from $$ \frac{d}{dt}\frac{\partial{L}}{\partial{\dot{q_i}}} - \frac{\partial{L}}{\partial{q_i}} = 0 $$

How can we get the corresponding Hamiltonian equation part? This is to prove $$ \dot{p'_i} = \frac{\partial{H'}}{\partial q_i} $$ $$ -\dot{q_i} = \frac{\partial{H'}}{\partial p'_i} $$

from

$$ \dot{p_i} = \frac{\partial{H}}{\partial q_i} $$ $$ -\dot{q_i} = \frac{\partial{H}}{\partial p_i} $$ where $p'_i = \frac{\partial L'}{\partial \dot q_i}$.

Edit

The corresponding $H'$ is $$ H' = \sum_k{p'_k \dot{q_k}} - L' $$ where $p'_k = \frac{\partial L'}{\partial \dot q_k}$.

$\endgroup$
  • $\begingroup$ For the "corresponding" part, do you know how the corresponding addition to the Hamiltonian looks like? I.e. how do we get $H'$ from $H$? How do you define $H'$ within the Hamiltonian formalism without referring to $L$ and $L'$? $\endgroup$ – ACuriousMind Jul 19 '14 at 16:38
  • $\begingroup$ Actually, the question is from Chapter 8 derivation 2 in Goldstein's Classical Mechanics, third edition. $\endgroup$ – Negelis Jul 19 '14 at 16:54
  • $\begingroup$ Hm. You're right (and I'm apparently a bit rusty in classical mechanics), I apologize. (I'll delete my wrong comments, no point in them cluttering this) I'm still not satisifed though, since $H'$ is defined in terms of $L'$, so it's a tautology that $H'$ fulfills Hamilton's equations since it is the Legendre transform of a valid Lagrangian for the system. $\endgroup$ – ACuriousMind Jul 19 '14 at 17:01
  • $\begingroup$ So the point is to prove H' fulfills Hamilton equation based on H fulfills Hamilton equation, not based on it is the Legendre transform of a Lagrangian L'. $\endgroup$ – Negelis Jul 19 '14 at 17:24
  • $\begingroup$ If anybody is interested in the solutions of exercise 8.2 in the Goldstein, you can find it as a spanish version here : github.com/nquesada/Goldstein/blob/master/capitulo08.pdf $\endgroup$ – Knowledge Nov 9 '15 at 8:42
2
$\begingroup$

As you state in the comments, $$ \frac{\mathrm dF}{\mathrm dt}=\frac{\partial F}{\partial q}\dot{q}+\frac{\partial F}{\partial t} $$ So popping this into the Lagrangian, $$ L'=L+\frac{\partial F}{\partial q}\dot{q}+\frac{\partial F}{\partial t} $$

The Hamiltonian $H=p\dot q-L$ implies $$ H'=p'\dot{q}-L'=p\dot q+something\tag{1} $$ where $something$ is for you to work out. Since $p=\partial L/\partial \dot q$, then we should assume that $p'=\partial L'/\partial\dot q$. It's not really necessary for this particular problem, but you can solve for $p'$.

The Hamiltonian formalism states that $q$, $\dot q$ and $p$ are independent, so we assume similarly that $q$, $\dot{q}$ and $p'$ are independent; hence $\partial L/\partial p=0\to\partial L'/\partial p'=0$.

So now all you have to do is solve $$ \frac{\partial H'}{\partial p'}\text{ and }-\frac{\partial H'}{\partial q} $$ using Eq. (1) to see if the transformation in the Lagrangian preserves the Hamiltonian EOM (hint: it does). Note also that I assume a single coordinate $q$, there really isn't much of a difference between $q_i$ for $i=1$ and $i\in(1,N)$.

$\endgroup$
1
$\begingroup$

If $$ L \to L' = L +\frac{dF(q,t)}{dt}$$ the corresponding Hamiltonian becomes $$ H \to H' = H - \frac{\partial F(q,t)}{\partial t} $$ as shown here. Moreover, the canonical momentum becomes $$ p \to P = p + \frac{\partial F}{\partial q} $$ while $$ q \to Q = q $$ as shown here.

These formulas allow us to check the invariance of Hamilton's equations explicitly. Concretely, \begin{align} \frac{dq}{dt} &= \frac{\partial H}{\partial p} \notag \\ \end{align} becomes \begin{align} \frac{dQ}{dt} &= \frac{\partial H'}{\partial P} \\ \therefore \quad \frac{dq}{dt} &= \frac{\partial \left(H - \frac{\partial F(q,t)}{\partial t} \right)}{\partial P} \\ \therefore \quad \frac{dq}{dt} &= \frac{\partial H}{\partial P} - \frac{\partial }{\partial P} \left( \frac{\partial F(q,t)}{\partial t} \right) \\ \therefore \quad \frac{dq}{dt} &= \frac{\partial H}{\partial P} \\ \therefore \quad \frac{dq}{dt} &= \frac{\partial H}{\partial p} \frac{\partial P}{\partial p} \\ \therefore \quad \frac{dq}{dt} &= \frac{\partial H}{\partial p} \quad \checkmark \end{align} where I used that $F$ does not depend on $P$ and $$\frac{\partial P}{\partial p} =\frac{\partial }{\partial p} \left( p+ \frac{\partial F}{\partial q} \right) = 1. $$

Analogously, we can check Hamilton's second equation: $$ \frac{dp}{dt}= -\frac{\partial H(q,p,t)}{\partial q} .$$ However, there is a subtlety. After the transformation, we have on the right-hand side $\frac{\partial H'(Q,P,t)}{\partial Q}$. But here we need take into account that $p$ also depends on $q$, since $ p \to P = p + \frac{\partial F(Q,t)}{\partial Q} $. Therefore \begin{align} \frac{\partial H'(Q,P,t)}{\partial Q} &= \frac{\partial H'(Q,p + \frac{\partial F}{\partial q} ,t)}{\partial Q} \\ &= \frac{\partial H'(Q,p,t)}{\partial Q} + \frac{\partial H(Q,p,t) }{\partial p} \frac{\partial p}{\partial Q} \\ &= \frac{\partial H(Q,p,t)}{\partial Q} - \frac{\partial^2 F(Q,t)}{\partial Q \partial t} + \frac{\partial H(Q,p,t) }{\partial p} \frac{\partial p}{\partial Q} \\ &= \frac{\partial H(Q,p,t)}{\partial Q} - \frac{\partial^2 F(Q,t)}{\partial Q \partial t} + \dot Q \frac{\partial \left(P- \frac{\partial F}{\partial q} \right)}{\partial Q} \\ &= \frac{\partial H(Q,p,t)}{\partial Q} - \frac{\partial^2 F(Q,t)}{\partial Q \partial t} - \dot Q \frac{\partial }{\partial Q} \frac{\partial F}{\partial q} \\ &= \frac{\partial H(Q,p,t)}{\partial Q} - \frac{d}{dt} \frac{\partial F}{\partial Q} \,. \end{align} where we used that $$ \frac{d}{dt} \frac{\partial F}{\partial Q}= \frac{\partial^2 F(Q,t)}{\partial Q \partial t} + \dot Q \frac{\partial }{\partial Q} \frac{\partial F}{\partial q} . $$

Using this, we can rewrite Hamilton's second equation after the transformation as follows: \begin{align} \frac{dP}{dt}&= -\frac{\partial H'(Q,P,t)}{\partial Q} \\ \therefore \quad \frac{d}{dt} \left( p+ \frac{\partial F(q,t)}{\partial q} \right) &= \frac{\partial H(Q,p,t)}{\partial Q} - \frac{d}{dt} \frac{\partial F}{\partial Q} \\ \therefore \quad \frac{dp}{dt} + \frac{d}{dt} \left(\frac{\partial F(q,t)}{\partial q} \right)&= \frac{\partial H(Q,p,t)}{\partial Q} - \frac{d}{dt} \frac{\partial F}{\partial Q} \\ \therefore \quad \frac{dp}{dt} &= -\frac{\partial H}{\partial q} \quad \checkmark \end{align}

EDIT: The subtlety was also noted here, but unfortunately without an answer and a few years ago there was even a paper which didn't notice it and claimed that Hamilton's equations are not invariant.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.